Flavonoids - From Biosynthesis to Human Health 2017
DOI: 10.5772/67809
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Profile of Red Maize Native from Mixteco Race and Their Antiproliferative Activity on Cell Line DU145

Abstract: Mexico is regarded as the point of origin and biodiversity of maize, which takes the colors white, yellow, blue, or red. Red maize in particular owes its coloring to a type of polyphenolic compounds known as anthocyanins. The aim of this study was to determine the proile anthocyanin of red maize, as well as their antiproliferative activity on prostate cancer cell line DU145. Three samples of red maize were analyzed. Total polyphenols, monomeric anthocyanins, antioxidant activity by DDPH and FRAP were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The in vitro cytotoxic activity of sclerin ( 1 ) and cyclosenegalin A ( 2 ) was assessed by XTT assay, using the prostate cancer cell line DU-145 [16,17]. As shown in Table 2, sclerin ( 1 ) and cyclosenegalin A ( 2 ) were able to inhibit cell proliferation of the human prostate cancer at μM concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro cytotoxic activity of sclerin ( 1 ) and cyclosenegalin A ( 2 ) was assessed by XTT assay, using the prostate cancer cell line DU-145 [16,17]. As shown in Table 2, sclerin ( 1 ) and cyclosenegalin A ( 2 ) were able to inhibit cell proliferation of the human prostate cancer at μM concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the chemical profile assessment of ACNs via HPLC-ESI-MS identified 20 compounds, characterizing cyanidin 3-p-hydroxy-benzoyl sophoroside-5-glucoside, C3G ( Figure 4 ), and cyanidin-3-O-(6′-acetyl-arabinoside) ( Figure 6 ) as major compounds. MTT assessments exerted significant antiproliferative activity and apoptosis effect in cell lines DU145 at 1000 μg/mL [ 65 ].…”
Section: Anti-prostate Cancer Properties Of Anthocyanidins/anthocyaninsmentioning
confidence: 99%